Utilization of Gamification in Arabic Language Learning to Increase Student Motivation and Achievement - Rezi, Melisa; Noor, Ahmad Firdaus Mohd; Nicholas, Tsai (Lughawiyah: Journal of Arabic Education and Linguistics, 2024)
Technological developments in the current era of globalization are essential in the world of Education. There is much technology that supports learning. In the current digital era, technology and Education have introduced gamification as an innovative method to increase student motivation and learning achievement in higher Education. However, gamification’s negative impact on academics still requires further research. This research aims to determine the effect of using gamification in increasing motivation and achievement. The method used in this research is a quantitative survey method. This method can show that this research is in the form of data containing numbers. This data was obtained by using Google Forms to create a questionnaire containing questions, which were then distributed to respondents who would get the results. So, the researchers will discuss these results in the results and discussion. The results of this research show and explain that gamification in learning Arabic can increase the interest, motivation, and achievement of college students in the Arabic language learning process. The conclusion of this research shows that gamification can increase enthusiasm for learning and student involvement in the learning process. The limitation of this research is that the researcher only focuses on the influence of gamification in increasing student motivation and achievement in higher Education. The researcher’s hope for future researchers is that they can further develop and explain in detail the influence of gamification in Arabic language learning to increase student motivation and achievement in higher Education.